The whaling season : - Mulvaney, Kieran (Island Press/Shearwater Books, 2003)
Despite a decades-long international moratorium on commercial whaling, one fleet has continued to hunt and kill whales in the waters surrounding Antarctica. Refusing to let this defiance go unchallenged, the environmental organization Greenpeace began dispatching expeditions to the region in an effort to intercept the whalers and use nonviolent means to stop their lethal practice. Over the past decade, Kieran Mulvaney led four such expeditions as a campaigner and coordinator. In The Whaling Season, he recounts those voyages in all their drama, disappointments, strain, and elation, giving readers a behind-the-scenes look at the hazards and triumphs of life as an environmental activist on the high seas. The author also explores the larger struggles underlying the expeditions, drawing on the history of commercial whaling and Antarctic exploration, the development of Greenpeace, and broader scientific and political efforts to conserve marine life. He presents a rich portrait of the current struggles and makes an impassioned plea for protection of some of the world’s most spectacular creatures. For armchair adventurers, polar enthusiasts, and anyone concerned about marine conservation and continued hunting of the world’s whales, The Whaling Season is an engrossing and informative tale of adventure set in one of the Earth’s last great wilderness areas